PROFIL LDII (LEMBAGA DAKWAH ISLAM INDONESIA) DI DESA SIALANG INDAH KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Vani Aprilia Masyitoh; T. Romy Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The background from this research is different ways of worshiping LDII (Lembaga Dakwah Islam Indonesia) religious groups. This research was conducted in Sialang Indah Village, Pangkalan Kuras District, Pelalawan Regency. The focus of this research is on the forms of special worship carried out by LDII members in Sialang Indah Village, the prayer procedures in LDII religious groups, and the marriage procession of LDII group members. This study aims to determine the types of LDII special worship groups that distinguish them from other religious groups, the procedures for praying in the teachings of the LDII group that distinguishes other Islamic organizations, and the marriage procession of the LDII group in Sialang Indah Village. The method used is qualitative descriptive. Data collection techniques used were observation, interviews with 5 informants, and documentation. The results of the study show that there are characteristics or special things in the LDII group that are routinely carried out, such as regular recitations conducted according to the age level of group members. Furthermore, differences in compulsory readings (one of them at Tahiyat prayer reading) and sunah (one of them is at the Iftitah prayer reading) in LDII group prayer, and matchmaking procession to the LDII group members' wedding, which in practice is arranged by the matchmaking team that has been formed in LDII's organizational structure.Keywords: LDII, Prayer, Marriage, Worship